Experimental and Computational Studies on the Reactivity of a Terminal Thorium Imidometallocene towards Organic Azides and Diazoalkanes1. (28th August 2014) - Ren, Wenshan; Zhou, Enwei; Fang, Bo; Hou, Guohua; Zi, Guofu; Fang, De‐Cai; Walter, Marc D.
Abstract The reaction of the base‐free terminal thorium imido complex [{η5‐1, 2, 4‐(Me3C)3C5H2}2ThN(p‐tolyl)] (1) with p‐azidotoluene yielded irreversibly the tetraazametallacyclopentene [{η5‐1, 2, 4‐(Me3C)3C5H2}2Th{N(p‐tolyl)NNN(p‐tolyl)}] (2), whereas the bridging imido complex [{[η5‐1, 2, 4‐(Me3C)3C5H2]Th(N3)2}2{μ‐N(p‐tolyl)}2][(n‐C4H9)4N]2 (3) was isolated from the reaction of 1 with [(n‐C4H9)4N]N3. Unexpectedly, upon the treatment of 1 with 9‐diazofluorene, the NN bond was cleaved, an N atom was transferred, and the η2‐diazenido iminato complex [{η5‐1, 2, 4‐(Me3C)3C5H2}2Th{η2‐[NN(p‐tolyl)]}{N(9‐C13H8)}] (4) was formed. In contrast, the reaction of 1 with Me3SiCHN2 gave the nitrilimido complex [{η5‐1, 2, 4‐(Me3C)3C5H2}2Th{NH(p‐tolyl)}{N2CSiMe3}] (5), which slowly converted into [{η5‐1, 2, 4‐(Me3C)3C5H2}{η5:κ‐N‐1, 2‐(Me3C)2‐4‐CMe2(CH2NNCHSiMe3)C5H2}Th{NH(p‐tolyl)}] (6) by intramolecular CH bond activation. The experimental results are complemented by density functional theory (DFT) studies.